Effect of financial literacy at consumptive behavior of ‘’X’’ university students in Medan City - Harkim Harkim; Bambang Sugiharto; Rejekia V Simanungkali; Ilhamsyah Siregar; Maya Andriani MEDIA (Enrichment : Journal of Management, 2023)
This study aims to examine the effect of financial literacy on the consumptive behavior of X university students in Medan city. The research is designed with a quantitative approach, where quantitative data is described with a correlational method. The population in this study were all students of the economic faculty at university X in Medan city, as many as 1181 people. The sample of this study was 95 students with a proportional stratified random sampling method. Data were obtained by distributing instruments in the form of questionnaires and direct documentation on other relevant sources. To analyze the data, structural equational modeling (SEM) technique was used. The results showed that financial literacy has a beta coefficient of -0.486 and has a t-value of 1.726>1.66. The calculation results mean that literacy has a negative and significant correlation or relationship direction.